Prepovedane droge in vožnja - Lovrečič, Mercedes (Zdravstveno varstvo, 2004)
Increase in illicit drug use in Europe could influence the safety in road traffic. The article presents epidemiological data, which notice the extensionof the problem, resume Slovenian legal issues regarding safety in road traffic and measures of the policemen at suspicion of drinking and drugged driving, resume statistical data of the General Police Office and Institute of Forensic Medicine about toxicological analysis of driver samples and accessible knowledge from researches about effects of some illicit drugs on driving skills. Collected data in Slovenia represent increasing trend of ordered tests and expertise examinations among drivers. It could indicate an increased driving under the influence of drugs among Slovenian drivers, but onthe other side the proportion of positive examined tests (alcohol in the range of 29,2% to 56,8%, other illicit drugs in the range of 19,8% to 26,5%) could also indicate on efforts and the awareness of Slovenian policeman to carry out adequate procedures and measures.
Keywords: cestni promet; droge; prometna varnost; psihoaktivne snovi; vožnja